The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/nu14030435
|View full text |Cite
|
Sign up to set email alerts
|

Glucoraphanin Increases Intracellular Hydrogen Sulfide (H2S) Levels and Stimulates Osteogenic Differentiation in Human Mesenchymal Stromal Cell

Abstract: Osteopenia and osteoporosis are among the most prevalent consequences of ageing, urging the promotion of healthy nutritional habits as a tool in preventing bone fractures. Glucosinolates (GLSs) are organosulfur compounds considered relatively inert precursors of reactive derivatives isothiocyanates (ITCs). Recent evidence suggests that GLSs may exert biological properties based on their capacity to release hydrogen sulfide (H2S). H2S-donors are known to exert anabolic function on bone cells. Here, we investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…All treatments were done in DM. Concentration and time of exposure for DEX-induced damage were previously set up [ 30 ]; glucoraphanin concentration was chosen based on the ability of the compound to increase the intracellular H 2 S concentration [ 84 ]; L-cysteine and 3-mercaptopyruvate concentrations were chosen based on previously obtained results [ 29 ].…”
Section: Methodsmentioning
confidence: 99%
“…All treatments were done in DM. Concentration and time of exposure for DEX-induced damage were previously set up [ 30 ]; glucoraphanin concentration was chosen based on the ability of the compound to increase the intracellular H 2 S concentration [ 84 ]; L-cysteine and 3-mercaptopyruvate concentrations were chosen based on previously obtained results [ 29 ].…”
Section: Methodsmentioning
confidence: 99%
“…The exploration of natural compounds and their analogs as chemopreventive agents is gaining momentum. SFN, known for its health benefits, is garnering attention in the medical field, especially for its potential protective effects against various types of cancer [38][39][40][41][42][43], cardiovascular diseases [44][45][46], neurological diseases [47][48][49][50], insulin resistance [51][52][53], obesity [54][55][56], and musculoskeletal diseases [57][58][59]. Additionally, the consumption of broccoli, brussels sprouts, cabbage, and SFN, an isothiocyanate derivative, is linked to various health benefits, including anticancer and antioxidant properties [60].…”
Section: Discussionmentioning
confidence: 99%
“…(Continued) (97); at the molecular level, SFN induced up-regulation of RUNX-2 in mouse MSCs (97). Gambari et al showed increased mineralization and BSP, CBS and SMAD-1 mRNA up-regulation by GRA administration in primary human MSCs (98). Finally, with regards to osteocyte regulation, Thaler et al showed that SFN inhibited proliferation in murine osteocyte-like cell line (MLO-Y4) (97).…”
Section: Decreased Viability and Osteoclastogenesismentioning
confidence: 99%
“…Gambari et al. showed increased mineralization and BSP, CBS and SMAD-1 mRNA up-regulation by GRA administration in primary human MSCs ( 98 ). Finally, with regards to osteocyte regulation, Thaler et al.…”
Section: Effect Of Oscs On Bone Tissue: Preclinical Evidencementioning
confidence: 99%
See 1 more Smart Citation